Strategic procurement and logistics management in the 21st Century a training guide on strategic procurement, logistics management and law procurement in 21st century - Orumwense, Jones (LAP Lambert Academy Publishing GmbH, 2012)
Organisations are increasing under pressure to operate efficient and effective strategies within the international market. They rely heavily upon the supply of goods and services to maintain competitive advantage.it is essential that procurement personnel develop an awareness of how strategies are developed and executed within the organisation, and the impact of strategic procurement and Logistics management upon the success of such strategies. The aim of the author is to provide students and professionals with the information and knowledge needed for an understanding of the nature of strategy within the organisation, and to develop knowledge of specific contribution that strategic management of the supply chain can make to overall success. The book has a new vision, added knowledge, optional insight and detailed input. The book is primarily intended to serve as a text for undergraduate, postgraduate and professionals in the industry